Moderating Effect of Organizational Culture on the Relationship between Reward System and Talent Engagement in Selected Private Technical and Vocational Education Training Institutions in Kenya - Gitonga, Christine Kananu; Egessa, Robert; Tibbs, Charles (Journal of Business and Social Review in Emerging Economies, 2024)
Purpose: This study sought to establish the influence of reward system on talent engagement and to establish the moderating effect of organizational culture on the relationship between employee value proposition and talent engagement of Technical And Vocational Education Training Institutions (TVET). Design/Methodology/Approach: The study was guided by theory of employee engagement. The study adopted causal research design. The study was conducted among 347 Private TVET in Nairobi County, Machakos County, Kiambu County and Kajiado County. The study used stratified random sampling to select 186 respondents. Data was collected using semi-structured questionnaires. Data analysis was done using descriptive and inferential statistics and presented using graphs, charts and tables. Findings: The results indicated the coefficient of determination (R2) was 0.271, P=0.000 and this shows that 27.1% of the variations in the talent engagement in private TVET can be explained by reward system.  The interaction between reward system and organizational culture moved R square from 0.271 to 0.646 implying that 37.6% of additional variation in talent engagement is as a result of moderating effect of organizational culture. Implications/Originality/Value: TVET management should make sure the incentive system fits with the fundamental values and corporate cultural concepts. Moreover, management of TEVT should emphasize the need of values in daily operations by including the incentive system within a values-driven corporate culture and encouraging and supporting actions related with the EVP.